Traumatic Brain Injury: in-hospital Survival Rates and the Main Predictors of in-hospital Mortality in Northeastern Brazil* - Pereira, Diego Henrique Gois; Neto, José Nolasco de Carvalho; Melo, Thaís Cristina de Souza; Santos, Catharine Natielle Oliveira Dias Belarmino dos; Silva, Elisa Ribeiro Carvalho; Oliveira, Arthur Maynart Pereira; Santos, Bruno Fernandes de Oliveira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Introduction Upper middle-income countries have epidemiological peculiarities that should be considered to identify the main predictive factors of intrahospital mortality regarding traumatic brain injury (TBI) to address modifiable problems.Objective To assess the in-hospital survival of patients with TBI and to identify the predictors of in-hospital death.Methods This is a retrospective dynamic cohort study of victims of TBI who were admitted to the Hospital de Urgência de Sergipe (HUSE, in the Portuguese acronym) between March 1, 2017 and April 29, 2018. The outcome considered was in-hospital death from any cause. Cox regression was used to assess predictors of in-hospital mortality.Results The sample comprised 596 patients, with a median age of 31.0 (12–94) years old, 504 (84%) of whom were men. Regarding TBI severity, 250 had mild TBI; 121 had moderate TBI; and 225 had severe TBI. The average follow-up was 20.6 ± 4.0 days, with 60 in-hospital deaths and a 30-day mortality of 22.9%. Four independent predictors of in-hospital death were identified: acute subdural hemorrhage (ASDH) (risk ratio [RR] = 1.926; 95% confidence interval [CI] = 1.15–3.22; p = 0.013), swelling (risk ratio [RR] = 3.706; 95%CI = 2.21–6.19; p < 0.001), skull fracture (RR = 2.551; 95%CI = 1.36–4.75; p = 0.003), and severe TBI (RR = 2.039; 95%CI = 1.29–4.12; p = 0.005).Conclusions Acute subdural hemorrhage, swelling, skull cap fracture, and a Glasgow Coma Scale score of < 9 at admission were independent predictors of in-hospital mortality in patients with TBI.
Keywords: developing country; mortality; survival; traumatic brain injury